Preparation of Graphene-ZnO Nanocomposites under Electric Furnace and Photocatalytic Degradation of Various Organic Dyes - Hwi Cho, Bum; Won Ko, Seung; Oh, Won-Chun; Bae Ko, Weon (Asian Journal of Chemistry, 2013)
The ZnO nanoparticles were synthesized by the reaction of an aqueous-alcoholic solution of zinc nitrate with sodium hydroxide under ultrasonic irradiation at room temperature. The graphene and zinc oxide nanocomposites were synthesized in THF and heated in an electric furnace at 700 ºC for 2 h. The graphene-ZnO nanocomposites were characterized by XRD, SEM and TEM. The catalytic properties of the graphene-ZnO nanocomposites in the photocatalytic degradation of the organic dyes, methylene blue, methyl orange and rhodamine B in every 5 min period under ultraviolet light at 365 nm were examined by UV-vis spectroscopy. The photocatalytic effect of the heated graphene-ZnO nanocomposites was compared with the unheated graphene-ZnO nanocomposites.